The Study of Improving Acid Mine Water Quality by Manganese Greensand and Activated Carbon Filtration - Mayabella Puspita Nugraha; Temmy Wikaningrum (Jurnal Serambi Engineering, 2022)
Bangka Belitung is one of the provinces in Indonesia known as a tin-producing area. Illegal tin mining results in excavated holes. The characteristics of the water in the ex-mining pits are acidic and contain heavy metals such as iron. This journal aims to determine the effect of filtration in improving the quality of water samples and to determine the best doses of Na2CO3 and KMnO4 as pre-treatment. Also to find out which experiment resulted in higher Fe removal efficiency and whether the quality of the treated water complies with the Regulation of the Minister of Health Number 492 of 2010. This study used primary data of pH and iron content as dependent variables. The population of this research is Alang Lake water that taken by random sampling method. The experiment was carried out on a lab-scale with two independent variables which were sampled with replicates every 30 minutes. In this experiment, the optimum doses of Na2CO3 and KMnO4 were 300 mg/L and 0.75 mg/L, respectively. The treated water has a pH value of 7.4-8.1, iron concentration 0.25 mg/L with removal efficiency is 93.56%, and turbidity 0.05-0.75 NTU. Thus, it can be said the dependent variables are in accordance with the relevant regulations.Keywords: Activated Carbon, Fe, Filtration, Manganese Greensand, Water Quality